Pengaruh Penggunaan Handphone Terhadap Prokrastinasi Akademik Siswa SMKN 1 Sumenep - nur haslinda; adirasa hadi prasetya; mafruhah mafruhah; anis tri yuliana (STKIP PGRI SUMENEP, 2022)
The purpose of this study was to determine the effect of using mobile phones on students' academic procrastination and to analyze the causes of student academic procrastination. The population of this study were all students of class XI at SMKN 1 Sumenep, while the sample was class XI students who were taken using Proportional Random Sampling technique with a total of 29 students. Data analysis was carried out by simple linear regression analysis using SPSS 25 software. The results showed that the use of mobile phones had a significant effect on students' academic procrastination with a significance level of 0.047. On the other hand, the cause of the birth of students' academic procrastination is the existence of pleasure-seeking or the behavior of doing activities that are considered more fun than doing academic assignments. Another reason is due to the dynamics of development and freedom that students have, they have a minimal sense of responsibility towards society and their families. Keywords: Mobile phone use, academic procrastination, pleasure-seeking.